Perancangan Media Promosi Digital Home Industries pada UMKM di Kota Medan - Pahlevi Pane, Reza; Elin Yuspita, Yulifda; Anggi Candra, Dwi (Yayasan Lembaga Studi Makwa, 2023)
Medan, North Sumatra, has great potential in the development of Micro, Small and Medium Enterprises (MSMEs), especially in home industries that produce local speciality products. However, challenges such as limited market access and low utilisation of digital technology are the main obstacles for MSME players in expanding marketing reach and increasing competitiveness. This research aims to design OpenCart-based digital promotional media as an innovative solution in supporting the development of MSMEs in the region. The research was conducted using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. At the analysis stage, the needs of MSME players and product characteristics were identified to ensure a relevant and effective solution. The design stage involves creating an OpenCart-based system designed to support product catalogues, online payment systems, as well as integration with social media. Next, the development stage realised key features tailored to user needs. System implementation is done through direct testing with MSME players in Medan. Finally, the evaluation stage measures the effectiveness of the platform through user feedback and sales data analysis. The results show that OpenCart-based digital promotion media can significantly increase the visibility of MSME products. Within the first three months, businesses reported an increase in sales of up to 25% thanks to the use of this platform. This research concludes that OpenCart-based digital promotional media can be a strategic step to support the digital transformation of MSMEs, improve competitiveness, and expand their marketing reach in the digital era.